Care coordination models for transition and long-term follow-up among childhood cancer survivors: a scoping review - Chi Kong Li; Cho Lee Wong; Carmen Wing Han Chan; William H C Li; Ka Ming Chow; Yin Ting Cheung; Mengyue Zhang; Eden Brauer; Yongfeng Chen (BMJ Open, 2024)
Objectives Childhood cancer survivors may experience complex health issues during transition and long-term follow-up (LTFU); therefore, high-quality healthcare is warranted. Care coordination is one of the essential concepts in advanced healthcare. Care coordination models vary among childhood cancer survivors in transition and LTFU. This study aimed to identify care coordination models for childhood cancer survivors in transition and LTFU and synthesise essential components of the models.Design This scoping review was guided by the methodological framework from Arksey and O’Malley and was reported with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. A systematic literature search was conducted on six databases using possible combinations of terms relevant to childhood cancer survivors, transition/LTFU and care coordination model. Data were analysed by descriptive and content analysis.Data sources The literature search was first conducted in May 2023 and updated in May 2024. Six databases including Medline, PubMed, Embase, Web of Science, CINAHL and Cochrane Library were searched; meanwhile, a hand search was also conducted.Eligibility criteria for selecting studies Studies relevant to describing any models, interventions or strategies about care coordination of transition or LTFU healthcare services among childhood cancer survivors were included.Data extraction and synthesis Two reviewers independently screened and included studies. Basic information as well as care coordination model-related data in the included studies were extracted. Descriptive summary and content analysis were used for data analysis.Results In the 20 545 citations generated by the search strategy, seven studies were identified. The critical determinants of the models in the included studies were the collaboration of the multidisciplinary team, integration of the navigator role and the provision of patient-centred, family-involved, needs-oriented clinical services. The main functions of the models included risk screening and management, primary care-based services, psychosocial support, health education and counselling, and financial assistance. Models of care coordination were evaluated at patient and clinical levels. Based on this review, core concepts of successful care coordination models for childhood cancer survivors in transition or LTFU were synthesised and proposed as the ‘3 I’ framework: individualisation, interaction and integration.Conclusion This scoping review summarised core elements of care coordination models for childhood cancer survivors’ transition and LTFU. A proposed conceptual framework to support and guide the development of care coordination strategies for childhood cancer survivors’ transition and LTFU care was developed. Future research is needed to test the proposed model and develop appropriate care coordination strategies for providing high-quality healthcare for childhood cancer survivors’ transition and LTFU.